Exploring the value of person-centred encounter groups today - relevance, purpose and importance. (2nd July 2020) - Haley, Jules; Yates, Rachel
ABSTRACT: In the first part of this personal reflective paper we describe setting up the 'Central London PCA Encounter Group' in the UK, which has been running monthly for the last two years. We explore the motivation for establishing the group, the ethos of facilitation, the challenges of the role of facilitators, conflict and the attitudinal qualities of the group, and the diversity and growth of the group. In the second part we introduce and look in detail at a short piece of qualitative research carried out with encounter group attendees, examining the five themes which emerged within the research: The Unknown, Connection, Belonging to a Group, Conflict, Self-Development and finally Conclusions.